Development and Characterization of Sol-Gel Spin Coated Zirconium Oxide Thin Films - Sankara Subramanian*, N.; Kavitha, A. (Asian Journal of Chemistry, 2013)
Zirconia (ZrO2) thin films have been prepared on glass substrate by the spin coating method at room temperature. The X-ray diffraction study of zirconia films confirms the tetragonal structure with preferred orientation along (111) plane. The crystallographic parameters viz., lattice constant, mean grain size, micro strain, dislocation density, texture coefficient and standard deviation have been calculated and the influence of number of coatings on the properties of the film have been discussed. The maximum optical transmittances of zirconia thin film have been found to 73 % at 350 nm wavelength. FT-IR spectrum results shows existence of band stretching corresponds to Zr-O group at 420 cm-1. The atomic force microscope image indicates smooth and uniform surface pattern without any pits of the pin holes.